Distribution of statistical observables for anomalous and nonergodic diffusions : from statistics to mathematics /: from statistics to mathematics. (2022) - Deng, Weihua; Wang, Xudong, 1992-; Nie, Daxin, 1993-; Liu, Xing, 1987-
No abstract available